(3GdeYLe GdUZjQs - (3SdjeGf Hf CMeO Hf CjhH Hf eWjQ GddNej GdTGej, CHh GdbGSe, J (B360 (3g` s
(3ChdgG (B:s
(3MOKfG YHO GdhgGH Hf eLOg GdMhWi Yf CfS Hf eGdc QVi Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:- ( (3SCdJ QHi YR hLd KdGKI NUGd aCYWGfi EKfjf heYfi hGMOI SCdJg Cf dGjSdW Ydi CeJi YOhkG ef ZjQge s
(3BNQgG (B:s
(3SeYJ UHMI HfJ CHj fYje GdaVd Hf Ocjf jbhd SeYJ CHj jbhd GdbQBf cdGe Gddg JYGdi ZjQ eNdhb JeJ BNQ GdeYLe GdUZjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAGJ Ydi GdMGaX CHj GdNjQ GHf GdLRQi GdTGaYi SfI (B838(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B121s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs